Gambling, Gaming, and Internet Behavior in a Sexual Minority Perspective. A Cross-Sectional Study in Seven European Countries - Broman, Niroshani; Prever, Fulvia; di Giacomo, Ester; Jiménez-Murcia, Susana; Szczegielniak, Anna; Hansson, Helena; Håkansson, Anders (Frontiers in Psychology, 2022)
Background: Addictive behavior of gambling, gaming and internet activity is partly a new research domain and has not been well investigated with regard to sexual minoirty populations. Although health disparities between sexual minorities and the general population are well documented, there is a lack of inclusion of sexual minorities in both research and clinic (Ash & Mackereth, 2013, Russel & Fish, 2016). Among lesbian, gay and bisexual populations certain features could be present that play a role for the development of addictive behaviours, such as social isolation and increased risk of other psychiatric problems. The aim of this study was to investigate problem gambling, problem gaming and problematic internet behaviour in a European context and if it is affected by sexual orientation status. Methods: An online web-survey was distributed among web-panels in England, Poland, Switzerland, Italy, Spain, Denmark and Sweden in 2017-2018. Result: 10 983 complete answers were collected. 7.1% of the participants had a sexual minority status (n=774). Regression models found that there was no difference in gambling, gaming and internet behaviour among heterosexual and sexual minority men. Sexual minority women were associated with problematic gambling (OR= 1.43) and gaming behavior (OR=1.79), when also controlling for age and nationality. When also controlling for psychological distress, women defining as having another sexual minority status than lesbian and bisexual remained significant for having a problematic gaming behavior (AOR= 2.4). Conlusion: An awareness of female sexual minority perspectives is relevant in facilities treating behavioural addiction as well as in future research in behavioural addiction. More research is needed in problematic gambling and gaming behaviour in different sexual minority populations with regard to psychiatric comorbidity and living conditions. An inclusion of sexual minority groups defining as other than gay and bisexual is needed in future research. No significant differences were found between heterosexual and sexual minority men in adjusted analysis in this study.